Dysplastic nevus associated with seborrheic keratosis - Luciane Francisca Fernandes Botelho; Nilceo Schwery Michalany; Milvia Maria Simoes e Silva Enokihara; Sergio Henrique Hirata (Sociedade Brasileira de Dermatologia, 2014)
Seborrheic keratosis is a common skin lesion which may coincidentally be associated melanocytic nevi. The authors describe a case of dysplastic nevus associated with seborrheic keratosis and discuss the clinical, dermoscopic, and histological findings of this association. They also discuss the association between seborrheic keratosis and other benign and malignant tumours.